2021
DOI: 10.1038/s41598-020-80579-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Berberis vulgaris L. root extract on ifosfamide-induced in vivo toxicity and in vitro cytotoxicity

Abstract: Ifosfamide is a widely used chemotherapeutic agent having broad-spectrum efficacy against several tumors. However, nephro, hepato, neuro cardio, and hematological toxicities associated with ifosfamide render its use limited. These side effects could range from organ failure to life-threatening situations. The present study aimed to evaluate the attenuating efficiency of Berberis vulgaris root extract (BvRE), a potent nephroprotective, hepatoprotective, and lipid-lowering agent, against ifosfamide-induced toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
(22 reference statements)
3
15
0
Order By: Relevance
“…All concentrations were found with better inhibitory profile Micrococcus luteus 16.81, 17.93, and 20.22 mm and Bacillus subtilis and 12.18, 16.72, and 18.37 mm, respectively. Similar trends were observed with the previously documented results of other species of Berberis [ 23 , 29 , 31 ]. The results suggested that root extract is a powerful source of wide-ranging antimicrobial agent.…”
Section: Discussionsupporting
confidence: 92%
“…All concentrations were found with better inhibitory profile Micrococcus luteus 16.81, 17.93, and 20.22 mm and Bacillus subtilis and 12.18, 16.72, and 18.37 mm, respectively. Similar trends were observed with the previously documented results of other species of Berberis [ 23 , 29 , 31 ]. The results suggested that root extract is a powerful source of wide-ranging antimicrobial agent.…”
Section: Discussionsupporting
confidence: 92%
“…The obtained results are in agreement with the recently reported antibacterial activity of the methanolic extract from the roots of B. baluchistanica against S. aureus, B. subtilis, P. aeruginosa, and E. coli with 30-, 22-, 19-, and 29mm zones of inhibition (Idrees et al, 2021). A similar trend of interactions was observed with the previously documented results of other species of Berberis (Ilyas et al, 2021). The results suggested that each extract possesses a broad spectrum of antimicrobial potentials.…”
Section: Discussionsupporting
confidence: 92%
“…About 60% of medications allowed for cancer treatment are of a natural source. The anticancer activity was not reported and published by other researchers to date, but different species of genus Berberis are reported to have in vitro cytotoxic activity against different destructive cell lines (El Fakir et al, 2021;Ilyas et al, 2021). An evaluation of the anticancer activity of the ethanolic extracts of the bark, leaves, and roots of the B. baluchistanica plant was done by using MTT cell assay against HeLa cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Many plants are the main sources for bioactive compounds that can be used to relieve diseases [ 81 ]. For instance, phytomedicine and plant-derived antioxidants are considered a prosperous strategy for alleviating chemotherapy-induced organ toxicities [ 28 , 82 , 83 , 84 , 85 ]. As a result, we aimed to evaluate the possible testiculo-protective effect of C. endivia L. crude extract, phenolic fraction, and isolated coumaric, vanillic, and ferulic acids against MTX-induced testicular injury in mice.…”
Section: Discussionmentioning
confidence: 99%